Low back pain and its determinants among wait staff in Gondar town, North West Ethiopia: A cross-sectional study - Yalew, Ermias Solomon; Adem, Kedir Sany; Kibret, Alemu Kassaw; Gashaw, Moges (Frontiers in Pain Research, 2022)
Background Low back pain is a common public health issue in the working population and one of the leading causes of disability. It is the leading cause of work-related conditions and the most common reason for filing a workers' compensation claim in low- and middle-income countries. Ethiopia is a developing country; there is a shortage of working materials, skilled labor, and a lack of awareness of ergonomics posture, which lead to lifting heavy objects, long periods of standing, repetitive twisting, and same sustained posture for long periods of time without a shift. As a result, the purpose of this study was to assess the prevalence and associated factors of work-related low back pain among restaurant wait staff in Gondar, Ethiopia, in the year 2019. Methods Institution-based cross-sectional study, including 420 restaurant wait personnel, was undertaken from 1 March to 30 April 2019. A simple random sampling procedure was used to choose the restaurants and wait staff. A standardized Nordic questionnaire was used to collect data. Data were entered into Epi Info 7 and analyzed in SPSS version 20. The univariate and multivariate logistic regression analyses were calculated. The significance of associations was reported by a P-value of < 0.05 and an adjusted odds ratio (AOR). The model fitness checked by the Hosmer–Lemeshow goodness of fit test was used. Result In this study, a total of 420 participants (99.53% response rate) ranging in age from 17 to 53 years old participated, with 184 (43.8%) participants reporting low back pain at some point in the past 12 months. Female participants had a higher prevalence of 130 (70.6%). Sex (AOR = 2.98; 95% CI: 1.07–8.30), frequent exercise (AOR 0.47; 95% CI: 0.24, 0.93), extended standing (AOR 8.82; 95% CI: 3.30, 20.32], and repetitive tasks (AOR 7.49; 95% CI: 4.29, 13.19) were all found to be significant predictors in low back pain. Conclusion More than two-fifth of waitresses and waiters reported low back discomfort at some point in the past 12 months. Predisposing factors for low back discomfort among restaurant wait staff included being female, standing for long periods of time while serving, and performing repetitive tasks. Regular exercise was found to be a protective factor against low back pain in wait staff. Delivering ongoing safety training is among the most potent essential measures required in preventing low back pain.